Temporal Trends of Insecticide Concentrations in Carpet Dust in California from 2001 – 2006 - Gunier, Robert B. (Environ Sci Technol, 2016)
Active ingredients in residential and agricultural insecticides have changed over time, due in part to regulatory restrictions. Few studies have evaluated how changes in active ingredients have impacted insecticide levels measured in homes. We measured concentrations of insecticides in one carpet dust sample from each of 434 homes in California from 2001 to 2006. Analytes included four insecticides sold for indoor home use during our study period (carbaryl, cypermethrin, permethrin and propoxur), and four no longer sold for indoor use including dichlorodiphenyltrichloroethylene (DDT, removed from the market in 1972), chlordane (1988), chlorpyrifos (2001), and diazinon (2004). We considered other potential determinants of concentrations of insecticides in carpet dust, such as home and garden use, occupational exposure, and nearby agricultural applications. We calculated percentage change in concentration of each insecticide per year, adjusting for significant determinants. In adjusted models, concentrations of insecticides in carpet dust decreased for three of four insecticides no longer sold for residential use: chlordane (−15%/year), chlorpyrifos (−31%), diazinon (−48%), and propoxur (−34%), which is currently sold for residential use but with increased restrictions since 1997. Concentrations of other insecticides sold for indoor use (carbaryl, cypermethrin, permethrin), and DDT, did not change over time in our study population.